2017
DOI: 10.1002/cncr.30958
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer mortality is higher in Filipinos in the United States: An analysis using national mortality records from 2003 through 2012

Abstract: Background Well-differentiated thyroid carcinoma has a favorable prognosis, but patients with multiple recurrences have drastically lower survival. Filipinos in the US are known to have high thyroid cancer incidence and recurrence rates. It is unknown whether Filipinos also have higher thyroid cancer mortality rates. Methods We studied thyroid cancer mortality in Filipino, non-Filipino Asian (NFA), and non-Hispanic White (NHW) adults using US death records (2003–2012) and US Census data. Age-adjusted mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
0
19
2
Order By: Relevance
“…Although some previous reports imply that the prognosis of TC mortality in men is poorly understood, contrary findings have also been reported [6,35,36]. Our findings differ from the widely held belief that men show poorer outcomes than women when diagnosed with TC [6,35]. Nevertheless, the underlying reason for mortality being higher in women than in men as observed in our study is unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although some previous reports imply that the prognosis of TC mortality in men is poorly understood, contrary findings have also been reported [6,35,36]. Our findings differ from the widely held belief that men show poorer outcomes than women when diagnosed with TC [6,35]. Nevertheless, the underlying reason for mortality being higher in women than in men as observed in our study is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the possible existence of a genetic predisposition in the host or a tumor that influences TC mortality, as described in other ethnicities [35] should not be ruled out. Along this line, the relative isolation of the afflicted areas (which were practically inaccessible until a few years ago) may be characterized by a tendency toward high consanguinity.…”
Section: Discussionmentioning
confidence: 99%
“…However, unexpected adverse pathologic features identified only on the final pathology report can often prompt return to the operating room for completion surgery. Asian patients especially are at an increased risk for differentiated thyroid cancers, and the literature suggests they can have worse disease‐specific outcomes . To our knowledge, this is the first study in the literature to evaluate for ethnic variations in adverse pathologic features in Chinese versus non‐Asian patients.…”
Section: Discussionmentioning
confidence: 96%
“…There are con icting reports on the effect of sex on mortality. Ito and Miyauchi [26] and Lin et al [27] found that a larger proportion of male than female patients died of thyroid cancer, whereas Nguyen et al [28] found the opposite result. Bray et al [25] reported that the mortality rates were similar in the sexes, based on global cancer statistics published in 2018.…”
Section: Discussionmentioning
confidence: 97%